Neck Circumference, a Novel Predictor of Overweight/ Obesity in School Children in Pokhara (Med Phoenix, 2020)
Background: Calculating BMI in an individual is a standard anthropometric procedure to estimate overweight/obesity. But it has been observed to be a bad predictor of central obesity. On the other hand, waist circumference, in many studies, has been found to be a good predictor of central obesity but not so frequently used because of tendency to vary throughout the day. In the recent years, NC has been found to have a good correlation with both BMI and WC. The aim of this study was to find out whether neck circumference is a good predictor of Overweight/Obesity or not.Methods: This was a cross sectional study carried out among the school children, aged 12 to 15 years, in Pokhara city, Nepal. In total, 408 students, 238 males and 170 females were screened. Anthropometric markers of obesity measured: included body mass index (BMI), waist circumference (WC), and compared with neck circumference (NC) of the same subjects. Pearson’s correlation test was used to see the correlation between NC with BMI and WC, and receiver operating characteristic curve analysis was used to determine the best cut off value of neck circumference in predicting high BMI.Results: Among 408 students, 238 (58.3%) were male and 170 (41.7%) were female. Among them 37 (9.1%) were overweight and 32 (7.8%) were obese. All the anthropometric parameters were significantly higher in cases, except height in male, than in controls. NC was significantly correlated with age, BMI, and waist circumference in both boys and girls. The best cut-off value of neck circumference by ROC to identify boys with a high BMI was 29.5 with sensitivity of (76%), specificity (54%), and for girls was 28.5 with sensitivity of (97%), specificity (48%).Conclusion: Statistically significant positive correlation was found between NC with BMI and WC. The value of NC as a screening tool has been found comparably lower in compare to WC.